2000
DOI: 10.1038/labinvest.3780071
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Tissue Localization of Membrane-Types 1, 2, and 3 Matrix Metalloproteinases in Rheumatoid Synovium

Abstract: SUMMARY:In vitro, membrane-type matrix metalloproteinases (MT-MMP) are known to activate the zymogen of MMP-2 (proMMP-2, progelatinase A), which is one of the key MMP in joint destruction in rheumatoid arthritis. In the present study, we examined the production and activation of proMMP-2, and the expression of MT1-MMP, MT2-MMP, and MT3-MMP, their correlation with proMMP-2 activation, and their localization in rheumatoid synovial tissue. Using sandwich enzyme immunoassay and gelatin zymography techniques, proMM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
55
1
3

Year Published

2001
2001
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(61 citation statements)
references
References 28 publications
2
55
1
3
Order By: Relevance
“…These MT-MMPs are present in rheumatoid and osteoarthritic tissues (53)(54)(55). MT1-MMP can cleave type II collagen (13), which is the major type of collagen in articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…These MT-MMPs are present in rheumatoid and osteoarthritic tissues (53)(54)(55). MT1-MMP can cleave type II collagen (13), which is the major type of collagen in articular cartilage.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, more than 30 y ago, Werb et al (30) and colleagues first demonstrated that human RA synoviocytes cultured under serum-free conditions and supplemented with plasminogen were able to mount potent collagenolytic activity. Although the relative roles of MMP-1 versus MMP-13 were not assessed in this model (MMP- 13 had not yet been identified), the issue of how the collagenase zymogen(s) might undergo extracellular activation in the presence of a relative excess of plasma antiproteinases was considered (30). In their study, the authors postulated that synoviocytes "penetrate" the antiproteinase shield by generating quantities of proteinases that exceed the local concentration of proteinase inhibitors (e.g., plasma proteinase inhibitors directed against plasmin or MMP-1, a 2 -antiplasmin, and TlMP-1, respectively, bind and inhibit target proteinases at a 1:1 molar ratio) (30,43).…”
Section: Discussionmentioning
confidence: 99%
“…Further, like the MMP family, the cysteine proteinases also comprise a large group of proteolytic enzymes, but only a single member of this gene family, termed cathepsin K, displays triplehelical collagenolytic properties (7,8). Significantly, all seven of these collagenases have been identified in the rheumatoid synovium at the mRNA or protein levels, or both (10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The precise role, however, that these enzymes play in RA synoviocyte-mediated tissue destruction remains the subject of speculation.…”
mentioning
confidence: 99%
“…MT-MMP-1 and MT-MMP-3 in particular have been detected at sites of destruction in rheumatoid arthritis (RA) (7,8). Several of these enzymes are currently considered therapeutic targets in arthritic diseases.…”
mentioning
confidence: 99%